Being an innovative and creative teacher: passion-driven professional duty - Žydžiūnaitė, Vilma; Arce, Ander (Creativity Studies, 2021)
The research problem relates to the lack of existing research in terms of understanding the meaning of being an innovative and creative teacher in association with a passion connected to professional duty. Research questions were the following: “What does it mean for a teacher to be innovative and creative? What makes an innovative and creative teacher?”. The aim was to explore the meaning of being an innovative and creative teacher through teachers’ experiences. The methodology was based on integration of practical phenomenology and epistemological phenomenology. The sample consisted of ten teachers from ten innovative Basque Country schools. Data was collected by using open-ended interviews. Findings showed that the passion-driven professional duty integrates being an ambitious professional, being professional through ethical and moral actions, endeavoring to discover students’ learning needs, designing learning environments, being coherent with school philosophy, and testing for improvement. Findings showed that a teacher’s innovativeness and creativeness are directed to the self, professional actions, students, school, and professional development. Conclusions are focused on empirical facts that innovative and creative teachers experience the meaning of their practices through duties, which they perform with passion. Teachers’ innovativeness and creativity are related to ethical, moral, professional, intellectual, social, institutional, individual, and processual needs.